As transformações do capitalismo em Campo Grande (MS): a construção social do trabalho por aplicativo sob a ótica dos motoristas - RANIELLY SILVA LEITE (2023)
The aim of this dissertation is to understand how app drivers in the city of Campo Grande - Mato Grosso do Sul, perceive themselves as workers. Work through apps is one of the new forms of informal, highly flexible work, and Uber Technologies Inc is one of its great examples, because it connects drivers and passengers who are in proximity through an app. When we think in the context of work platformization, this change occurred differently in each state and city in Brazil. In Campo Grande, Mato Grosso Do Sul, Uber started operating in 2016, followed by other transport applications. In 2022, it is stipulated that the number of drivers registered in the application will be more than 10 thousand. To better understand the transformations in the world of work, at first, this dissertation presents a brief historical context of the transformation of work from the changes of capitalism. Interviews were carried out from 2020 to 2022 that permeate the discussion of this dissertation, through speeches and stories of application drivers in Campo Grande - MS, which inform us how they perceive themselves as workers, the profile of these interviewees, their individual and collective demands, their experiences during the pandemic and the regulation of these professionals in the capital of Mato Grosso do Sul.